NManagement Board Composition of Banking Institutions and Bank Risk-Taking: The Case of the Czech Republic - Diana Zigraiova (Charles University in Prague, Institute of Economic Studies (IES), 2016)
The paper investigates how management board composition of banking institutions impacts their risk-taking behavior in the Czech Republic. More specifically, we examine the effect of average director age, proportion of female directors, non-national directors and proportion of their attained education on four different bank risk proxies. We build a unique data set comprising selected biographical information on management board members of the Czech financial institutions holding a banking license over 2001-2012 period. For the Czech banking sector overall, we find that higher proportions of non-national directors increase bank risk measured by profit volatility and decrease bank stability captured by Z-score. Similarly, a larger proportion of directors holding an MBA raises bank riskiness measured by profit volatility. On the other hand, the presence of directors holding a PhD on boards of large Czech banks enhances bank stability captured by Z-score. Moreover, we detect risk-enhancing implications of board size for the segments of building savings societies and small and midsized banks. As for average board tenure, its effect on risk-taking varies depending on bank characteristics. We find mixed evidence on the effect of female directors and do not find any strong effect of directors' age on risk in the Czech banking sector.
Keywords: C33; G21; G34; J16; 330; management board composition; banks; risk-taking; panel data